Sexual and gender minority stigma and motivating beliefs among the general public in Rwanda - Muhire, Gustave; Karanja, Ann Chereen; Habimana, Odile; Turatsinze, Everest; Kansiime, Deborah; Twahirwa, Louange Gutabarwa; Favina, Alain; Mukashyaka, Ritah; Niyotwagira, Egide; Kagaba, Aflodis; Kageha Igonya, Emmy; Otukpa, Emmanuel; et al. (Frontiers in Sociology, 2025)
BackgroundSexual and gender minorities (LGBTQ+) individuals in Rwanda face significant stigma and discrimination, driven by stigmatizing sociocultural and religious norms. This study investigates public perceptions toward sexual and gender minorities (LGBTQ+) in Rwanda, focusing on exploring non-discrimination beliefs, acceptance levels, and views on whether LGBTQ+ identities are innate.MethodologyA cross-sectional study was conducted across six districts in Rwanda, with 1,254 non-LGBTQ+ participants using convenience and snowball sampling. Descriptive statistics, ANOVA, and multivariable linear regression analyses were performed to assess associations between non-discrimination beliefs, acceptance, beliefs about being born LGBTQ+, and sociodemographic factors.ResultsThe average LGBTQ+ acceptance score was 8.7 out of 15 (Stdev: 3.6). Beliefs that one is born LGBTQ+ had an average score of 6.0 out of 10 [Sdev=2.2]. Regarding beliefs that one should not discriminate against LGBTQ+ the average score was 28.0 [Stdev: 8 out of 39.2]. Every one-point increase in people's beliefs about not discriminating against LGBTQ+, their acceptance of LGBTQ+ people increases by 0.25 points [95% CI (0.23, 0.27)]. As people's beliefs about not discriminating against LGBTQ+ increased by one point their belief that LGBTQ+ are born as such increases by 0.11 points [95% CI (0.10,0.12)].ConclusionMost Rwandans sampled have non-discriminatory attitudes, however the acceptance of LGBTQ+ persons and beliefs that being LGBTQ+ is innate remains low. As non-discriminatory beliefs improve so does acceptance of LGBTQ+ and the belief that it is an innate identity. The findings suggest that educational and sensitivity efforts might be worth exploring as they could potentially improve attitudes toward perceptions and acceptance toward LGBTQ+ individuals, but experimental research would be needed to test this possibility.